Exosomal non-coding RNAs: a new avenue for treating diabetic foot ulcers - Chen, Guohao; Chen, Gang; Lu, Jun; Hu, Shaolong (Frontiers in Molecular Biosciences, 2025)
Diabetic foot ulcer (DFU) is a severe complication resulting from diabetes mellitus (DM) that affects approximately 18.6 million individuals annually and has a lifetime incidence of up to 25% among DM patients. These ulcers often precede lower-extremity amputations and are associated with high mortality as well as economic burden that necessitate innovative therapeutic strategies beyond conventional methods. Recent research efforts have highlighted the potential of non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), that regulate gene expression and cellular functions critical for wound healing. Exosomes are the natural carriers of ncRNAs and offer a promising avenue for the treatment of DFU by enhancing the stabilities and bioavailabilities of these molecules. In this review, we explore the substantial potential of ncRNAs in DFU treatment by emphasizing the action mechanisms of ncRNAs, refinement of exosome-based delivery systems, and expansion of clinical trials to translate ncRNA-based therapies into clinical practice. The application of exosomal ncRNAs involves diverse strategies through different mechanisms, although there remain challenges in terms of exosome preparation consistency, functional enhancement, and efficient drug delivery. The future directions in this regard include optimizing isolation techniques, engineering exosomes for improved targeting, integrating with biomaterials, and conducting more clinical trials to validate safety and effectiveness, thereby paving the path for widespread clinical use.